OPTIMAL CONTROL STRATEGY WITH MULTI-DELAY IN STATE AND CONTROL VARIABLES OF A DISCRETE MATHEMATICAL MODELING FOR THE DYNAMICS OF DIABETIC POPULATION. (2020) - KOUIDERE, ABDELFATAH; LABZAI, ABDERRAHIM; KHAJJI, BOUCHAIB; FERJOUCHIA, HANANE; BALATIF, OMAR; BOUTAYEB, ABDESSLAM; RACHIK, MOSTAFA
No abstract available